Handbook of child language disorders - Schwartz, Richard G. (Psychology Press, 2009)
Reviews research concerning the nature, assessment, and remediation of language disorders in children. This book includes chapters focusing on specific groups of childhood disorders (SLI, autism, genetic syndromes, dyslexia, hearing impairment); the linguistic, perceptual, genetic, neurobiological, and cognitive bases of these disorders.